2009
DOI: 10.2131/jts.34.699
|View full text |Cite
|
Sign up to set email alerts
|

Carbonated soft drinks and carbonyl stress burden

Abstract: -Carbonated soft drinks reportedly contain methylglyoxal (MG), which is strongly associated with human carbonyl stress. We sought to evaluate the effects of carbonated drink intake on human carbonyl stress. We measured MG levels in 4 commercial beverage brands, and evaluated the changes in plasma MG in healthy subjects following the intake of carbonated drinks. By 30 min after intake of samples containing high glucose and high MG, the levels of plasma MG, glucose, insulin and uric acid had -bonated samples con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…This finding could be due to absorption of dietary MGO, but may more likely result from an increased glycolytic flux due to ingestion of carbohydrates. 39 The latter conclusion is supported by studies of Beisswenger et al, who detected a postprandial increase in plasma MGO levels following a carbohydrate-rich rest meal. 40 In an animal study with rats, Golej et al observed that daily amounts of 0.7 mmol MGO/kg body weight orally administered over 5 months induced pathological changes in the kidneys of the animals (glomerular basement membrane thickening), indicating a possible absorption of ingested MGO and transfer to the kidneys.…”
Section: ■ Results and Discussionmentioning
confidence: 77%
“…This finding could be due to absorption of dietary MGO, but may more likely result from an increased glycolytic flux due to ingestion of carbohydrates. 39 The latter conclusion is supported by studies of Beisswenger et al, who detected a postprandial increase in plasma MGO levels following a carbohydrate-rich rest meal. 40 In an animal study with rats, Golej et al observed that daily amounts of 0.7 mmol MGO/kg body weight orally administered over 5 months induced pathological changes in the kidneys of the animals (glomerular basement membrane thickening), indicating a possible absorption of ingested MGO and transfer to the kidneys.…”
Section: ■ Results and Discussionmentioning
confidence: 77%
“…MG is mainly derived from glycolysis[2] and increasing evidence reveals that MG can be generated by degradation of carbohydrates in foods and beverages such as soy sauces and coffee[3], [4]. MG attacks the arginine, lysine and cysteine residues of proteins to form irreversible advanced glycation end products (AGEs), which subsequently leads to more cross-linking and degradation of proteins[5].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, glucose-containing carbonated soft drinks increase carbonyl stress burden (3) , which, in turn, may result in a decrease in antioxidant concentration in oral saliva (4) and enhance oxidative nitration in association with the inflammatory reaction (5) . From the biological viewpoint, the inflammatory reaction caused by such oxidative stress is highly associated with systemic diseases, such as metabolic syndrome, diabetes, hypertension, asthma and periodontal disease (PD) (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) .…”
mentioning
confidence: 99%
“…From the biological viewpoint, the inflammatory reaction caused by such oxidative stress is highly associated with systemic diseases, such as metabolic syndrome, diabetes, hypertension, asthma and periodontal disease (PD) (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) . Oxidative stress (2,3,6,8,9,(13)(14)(15) pertaining to PD may be mediated through advanced glycation end-products that are created through non-enzymatic pathways from monosaccharide substances, dicarbonyls originating from the Maillard reaction, sugar self-oxidation and other molecular pathways (16,17) . Several studies show a link between soft drinks and systemic disease (18,19) , but the specific association between the intake of soft drinks and PD has not been investigated yet.…”
mentioning
confidence: 99%
See 1 more Smart Citation